Locked in the Home: A Critique of House Arrest as an Alternative to Imprisonment for Women Sentenced for Drug-Related Crimes - Ariza, Libardo José (The prison journal, 2021)
This article addresses the unintended consequences of using house arrest for female offenders as an alternative to prison for drug-related crimes. We propose that in patriarchal societies, locking women at home could imply moving them to another control device that may be as harmful as prison. Thereby, house arrest creates an unintended effect in which domestication in traditional gender roles ends up being the primary target of female offender punishment.